Microstructure and failure mechanism of FGH96 solid-state diffusion bonding interface - YANG Jie; LIU Guang-xu; ZHANG Jing; WANG Wen-ying; WANG Xiao-feng; ZOU Jin-wen (Fenmo yejin jishu, 2021)
The microstructure on the solid-state diffusion bonding interfaces of the initially as-forged, as-solution, and sub-aging FGH96 was characterized, the tensile properties of the bonding interfaces were tested, and the failure behavior was studied. It is found that the good metallurgical bonding is achieved at the bonding interfaces of all the three primitive state specimens after the solid-state diffusion, and no cracks and cavities are found. The interfaces of the as-forged specimens show more sufficient diffusion of elements and smoother transition of microstructure, while the interfaces of both the as-solution and sub-aging specimens exhibit an obvious bonding effecting zone. After the solid-state diffusion bonding and the standard heat treatment, the second γʹ phases in the as-forged specimens are fine, uniform, and spherical. However, the second γʹ phases in the as-solution and sub-aging specimens grow up and split up because of the solid-state diffusion bonding thermal cycle. Different morphology of the second γʹ phases causes the difference of properties in the bonding interface regions. Results of the electron backscattered diffraction (EBSD) show that the preferred orientation of large grains is {100}, and the grain orientation is more obvious as the closer distance to the solid diffusion interface. The tensile test results show that the strength at the interfaces of the forged specimens after the solid-state diffusion bonding and the standard heat treatment is more than 99% of that of the matrix. The tensile cracks mainly initialize from the aggregated area of the large grains and the coarse γʹ phases, which show the transgranular dimple fracture behavior.